LO015: A multi-centered regional emergency department study of renal colic management using medical expulsion therapy. (2nd June 2016) - Bristow, E.; Kinnaird, A.; Schuler, T.; Pang, P.; Couperthwaite, S.; Villa-Roel, C.; Rowe, B.H.
Abstract : Introduction: Patients with renal colic present frequently to the emergency department (ED). Existing literature suggests management with medical expulsion therapy (MET) may improve outcomes, especially for those with stones > 5 mm in size. This study evaluates the use of MET in the management of adult patients seen in regional EDs with a diagnosis of renal colic.Methods: A multi-centered medical chart review study was conducted in seven Edmonton-Zone EDs. Approximately 100 cases from each site were randomly selected from administrative data from the 2014 calendar year, no repeat cases were permitted. Using a standardized data collection process and trained research assistance, data were abstracted from medical charts. Medians and inter-quartile ranges (IQR), proportions, and odds ratios (OR) with 95% confidence intervals (CIs) are reported.Results: Overall, 656 patient charts were included in the review; median age was 46 years (IQR: 35, 46) and 249 (38%) were female. Few (10%) arrived by ambulance or were on MET therapy at presentation; however, many (51%) reported a previous episode of renal colic. Many (191 29%) received no initial ED imaging; CT (236 36%) was favoured over ultrasound (39 6%) for initial imaging, either alone or with plain radiographs (8%). Plain radiographs were frequently ordered (204 31%). Only 198 (31%) of charts contained documentation of the use of MET at discharge and the median duration of therapy was 10 days (IQR: 7, 14). Initiation of MET therapy did not vary based on older age (OR = 0.8; 95% CI: 0.57, 1.14); sex (OR = 0.9; 95% CI: 0.67, 1.33); resident involvement (OR = 1.1; 95% CI: 0.63, 2.0); presentation to an academic centre (OR = 1.4; 95% CI: 0.96, 1.95) or stone size (OR = 1.3; 95% CI: 0.76, 2.06).Conclusion: Management of renal colic with MET is uncommon in this region and practice variation appears driven by physician preference rather than evidence. Practice guidelines with standardized order sets are urgently needed to improve care.